2008
DOI: 10.1111/j.1365-3164.2008.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyzine and cetirizine pharmacokinetics and pharmacodynamics after oral and intravenous administration of hydroxyzine to healthy dogs

Abstract: Pharmacokinetic parameters of hydroxyzine and its active metabolite cetirizine were determined after oral and intravenous administration of 2 mg kg(-1) of hydroxyzine to six healthy dogs. Plasma drug levels were determined with high-pressure liquid chromatography. Pharmacodynamic studies evaluated the suppressive effect on histamine and anticanine IgE-mediated cutaneous wheal formation. Pharmacokinetic and pharmacodynamic correlations were determined with computer modelling. The mean systemic availability of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 34 publications
4
52
1
Order By: Relevance
“…3). The antihistamine response in this study is consistent with the reported antihistamine response to cetirizine after administration of 2 mg/kg hydroxyzine per os daily in dogs, while medication with 1 mg/kg cetirizine orally once daily results in a lower antihistamine response [10, 12]. These conflicting results may be explained by insufficient plasma exposure when lower doses of cetirizine than in this study are used.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…3). The antihistamine response in this study is consistent with the reported antihistamine response to cetirizine after administration of 2 mg/kg hydroxyzine per os daily in dogs, while medication with 1 mg/kg cetirizine orally once daily results in a lower antihistamine response [10, 12]. These conflicting results may be explained by insufficient plasma exposure when lower doses of cetirizine than in this study are used.…”
Section: Discussionsupporting
confidence: 83%
“…These conflicting results may be explained by insufficient plasma exposure when lower doses of cetirizine than in this study are used. Due to the fairly long half-life (median 10 h) of cetirizine, 2 mg/kg daily dose is sufficient to maintain plasma concentration exceeding the median IC 50 value (0.33 µg/mL) for 24 h. This quantitative information is similar to the median half-life of cetirizine (9.7 h) and the IC 50 -value (0.6 µg/mL), after administration of hydroxyzine, reported by Bizikova et al [12]. …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A number of analytical methods have been used to quantify cetirizine in pharmaceutical formulations and biological fluids (serum, plasma, urine, and tears) including high performance thin layer chromatography (HPTLC) [6], gas chromatography [7], HPLC with ultraviolet detection [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], HPLC with fluorescence detection (pre-column derivatization) [25], HPLC with on-line liquid scintillation counting [26], and capillary electrophoresis (CE) [14,[27][28][29]. However, these methods have a number of disadvantages; for example, they require a large volume of sample (≥1.0 mL), and have long run time, low separation resolution, and poor sensitivity.…”
Section: Introductionmentioning
confidence: 99%